2015
DOI: 10.1007/s11412-015-9208-0
|View full text |Cite
|
Sign up to set email alerts
|

Appropriation of a representational tool in a second-language classroom

Abstract: While the affordances of face-to-face and online environments have been studied somewhat extensively, there is relatively less research on how technology-mediated learning takes place across multiple media in the networked classroom environment where face-to-face and online interactions are intertwined, especially in the context of language learning. This case study contextually investigates the appropriation of a representational tool by students in small groups, in the context of collaborative second languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Bere and Rambe (2016) said MIM had the potential to build a flexible learning environment to assist reformation from teacher-centered to student-centered learning in higher education, which could offer students more participation and engagement in tasks, deepening knowledge and prompting interest in learning. Finally, Wen, Looi, and Chen (2015) found that embedding GS, a representational tool, in a collaborative language (Chinese) learning environment enabled junior students to participate equally, collect and share ideas based on individual effort and social sharing, guide collaborative interaction, and facilitate their language learning skills.…”
Section: What Kinds Of Learning Environments Have Been Used For Exploring Triggers?mentioning
confidence: 99%
“…Bere and Rambe (2016) said MIM had the potential to build a flexible learning environment to assist reformation from teacher-centered to student-centered learning in higher education, which could offer students more participation and engagement in tasks, deepening knowledge and prompting interest in learning. Finally, Wen, Looi, and Chen (2015) found that embedding GS, a representational tool, in a collaborative language (Chinese) learning environment enabled junior students to participate equally, collect and share ideas based on individual effort and social sharing, guide collaborative interaction, and facilitate their language learning skills.…”
Section: What Kinds Of Learning Environments Have Been Used For Exploring Triggers?mentioning
confidence: 99%
“…The CSCL community has recognized that teachers have a double role as a designer and as a user of VLEs -(e.g. Hamid et al, 2014;Wen et al, 2015). This can be seen as a type of end-user development: teachers actively tailor the environment as they customize VLE tools, and integrate them into their course designs (Mørch, 1997).…”
Section: Teachers' Appropriation and End User Developmentmentioning
confidence: 99%
“…Research into teachers' use and appropriation of educational technology has focused on various aspects, including pedagogy (e.g., Berggren et al, 2005;Bennett et al, 2015), institutional policies (Bennett et al, 2011) and how the interaction between teacher and students shapes the use of educational tools (Wen et al, 2015). This research has clarified how teachers set educational goals (what should an activity achieve for students?…”
Section: Teachers' Appropriation and End User Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies done in collaborative writing are focusing more into students' attitude and scrutinizing of the endproduct as opposed to evaluating the nature of the collaboration process when students are working together (Wen, Looi & Chen, 2015).…”
Section: Background Of the Studymentioning
confidence: 99%